Dimensi Violatif dalam Politik Indonesia Tahun 2024: Violent Dimensions in Indonesian Politics in 2024 - Jama, Andreas; Riyanto, Armada (Jurnal Filsafat Indonesia, 2025)
This research focuses on the theme of the relationship between violative dimensions and politics. The aim is to confirm one viewpoint stating that politics has violative dimensions. By that, it means that politics is susceptible to violence, manipulation, intrigues, dirty strategies, systematic injustice, confusion, or chaos. Politics never truly escapes from these violative dimensions involving the aforementioned aspects. Anomalies tend to occur in politics. The methodology used in this research is literature review. The author then correlates this viewpoint with the implementation of politics in Indonesia in 2024. The author uses various issues or violations that occur in the implementation of politics in Indonesia as a measure to determine the validity of this viewpoint. This research finds that this viewpoint is undoubtedly valid. Violative dimensions can be said to be a vital or integral part of politics. They are like two sides of the same coin, coexisting. In other words, this viewpoint is a commonly accepted opinion that can be justified by everyone.